Non-invasive High Frequency Repetitive Transcranial Magnetic Stimulation (hfrTMS) Robustly Activates Molecular Pathways Implicated in Neuronal Growth and Synaptic Plasticity in Select Populations of Neurons - Fujiki, Minoru; Yee, Kelly Matsudaira; Steward, Oswald (Frontiers in Neuroscience, 2020)
Patterns of neuronal activity that induce synaptic plasticity and memory storage activate kinase cascades in neurons that are thought to be part of the mechanism for synaptic modification. One such cascade involves induction of phosphorylation of ribosomal protein S6 in neurons due to synaptic activation of AKT/mTOR and via a different pathway, activation of MAP kinase/ERK1/2. Here, we show that phosphorylation of ribosomal protein S6 can also be strongly activated by high frequency repetitive transcranial magnetic stimulation (hfrTMS). HfrTMS was delivered to lightly anesthetized rats using a stimulation protocol that is a standard for inducing LTP in the perforant path in vivo (trains of 8 pulses at 400 Hz repeated at intervals of 1/10 s). Stimulation produced stimulus-locked motor responses but did not elicit behavioral seizures either during or after stimulation. After as little as 10 min of hfrTMS, immunostaining using phospho-specific antibodies for the phosphorylated form of ribosomal protein S6 (rpS6) revealed robust induction of rpS6 phosphorylation in large numbers of neurons in the cortex, especially the piriform cortex, and also in thalamic relay nuclei. Quantification revealed that the extent of the increased immunostaining depended on the number of trains and stimulus intensity. Of note, immunostaining for the immediate early genes Arc and c-fos revealed strong induction of IEG expression in many of the same populations of neurons throughout the cortex, but not the thalamus. These results indicate that hfrTMS can robustly activate molecular pathways critical for plasticity, which may contribute to the beneficial effects of TMS on recovery following brain and spinal cord injury and symptom amelioration in human psychiatric disorders. These molecular processes may be a useful surrogate marker to allow optimization of TMS parameters for maximal therapeutic benefit.